Global existence and uniqueness of a periodic wave solution of the generalized Burgers–Fisher equation. (November 2021) - Zhang, Huiyang; Xia, Yonghui; N'gbo, Paul-Rene
Abstract: In this paper, we investigate the global existence and uniqueness of a periodic wave solution of the generalized Burgers–Fisher equation. We prove that the generalized Burgers–Fisher equation admits an isolated periodic wave solution based on the monotonicity of the ratio of two Abelian integrals.